INVESTASI PADA GENERASI MILENIAL: FAKTOR YANG MEMPENGARUHI MINAT GENERASI MILENIAL UNTUK BERINVESTASI REKSADANA SYARIAH - Aldila Viddy Raihan Rosandya; Mohamad Soleh Nurzaman (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
The growing development of Islamic mutual funds makes Islamic capital marketinstruments more varied and more promising for investors who want to investtheir capital in the Islamic capital market. Indonesia's great potential as thelargest Muslim country globally should make Indonesia one of the centers for thedevelopment of the sharia-based financial industry, including the world's capitalmarket. The purpose of this study is to analyze the factors that influence theinterest of investors, especially the millennial generation to invest in Islamic mutual funds, analysis of the significance of the factors that influence investors'interest in investing in Islamic mutual funds and analysis of the relationship thataffects the factors that influence investors' interest in investing. The method usedis quantitative, outer model approach, inner model, and hypothesis testing. Theresults obtained in this study there are two accepted hypotheses, namely theproduct information variable (X1) and Economic Considerations (X4) inhypotheses H1 and H4, which influence investment decisions, and the rejectedvariables in H2 and H3 are Investment Risk (X2) and Consideration ShariaPrinciples (X3) on investment decisions